Implementasi sistem informasi akuntansi untuk meningkatkan akuntabilitas laporan keuangan - Rini Wahyuningsih (Department of Accounting Universitas PGRI Yogyakarta, 2023)
Accounting in MSMEs includes financial recording and reporting which is useful for the decision-making process, but to date there are still many MSMEs that have not implemented an accounting system. Bookkeeping is only limited to recording income and expenses, so it is not effective and efficient. Therefore, in recording transactions and preparing financial reports, accounting software is needed to support business development. This research aims to determine the importance of implementing an accounting information system, as well as to determine the ability of an accounting information system to produce accountable financial reports. This research was conducted at LPK Pacific Marine School Yogyakarta for three months in order to implement the Integrated Work Learning Program (PBBT) using qualitative descriptive research methods. The type of data used is primary data obtained from interviews and observations, as well as secondary data obtained from internal company sources and research-related literature. The results of this research show that companies still need an accounting system in preparing financial reports. Then, after implementing an accounting information system with Zahir Accounting Personal 6 software, the company can present the resulting financial report, namely in the form of financial position and Income statement.